MIMO Steim: The artist is telepresent - Nunes, Fabio Oliveira [UNESP] (Association for Computing Machinery (ACM), 2017)
MIMO Steim presents himself as a young technological artist. This artist decides to suspend all direct personal contact through the proposition of a teleperformance in which he would stay uninterruptedly online chatting with interlocutors through a chat room present on his personal website, called The artist is telepresent (2013) . MIMO, in fact, is a chatbot who pretends to be an artist. This is a proposal to exhibit the fake teleperformance as an installation with digital projection.
Keywords: AIML; Chatbots; Web art